Color stability of the artificial iris button in an ocular prosthesis before and after acrylic resin polymerization - Moreno, Amália [UNESP]; Goiato, Marcelo Coelho [UNESP]; Oliveira, Kamila Freitas [UNESP]; Iyda, Mariana Garib [UNESP]; Haddad, Marcela Filié; Dekon, Stefan Fiuza de Carvalho[UNESP]; Santos, Daniela Micheline dos [UNESP] (Elsevier B. V., 2015)
This study investigated the effects of the ocular prosthesis fabrication technique and the paint on the color stability of the artificial iris button before and after polymerization of the colorless resin. Sixty samples simulating artificial eyes were made, including 30 samples with blue- and 30 samples with sepia-colored artificial irises. Ten samples were made by each of three techniques (i.e., conventional, prefabricated cap, and inverted painting) for each color. The color of the artificial iris button was measured through reflection spectrophotometry by the CIE L*a* b* system before and after polymerization of the prosthesis (colorless resin). Data were evaluated by analysis of variance (ANOVA) and the Tukey honestly significant different (HSD) tests (α=0.05). All of the samples exhibited color changes. Samples made by the prefabricated cap technique exhibited the highest color change values for both colors (P<.05). The inverted painting technique exhibited the lowest color change values for the sepia-colored artificial irises (P<.05). Sepia-colored artificial irises exhibited lower color change values than blue-colored artificial irises for both techniques (P<.05). In conclusion, the technique used to obtain the ocular prosthesis significantly affected the stability of the artificial iris color for each color tone and the conventional technique and the painting technique inverted were considered clinically acceptable for sepia color.
Keywords: Acrylic resins; Artificial eye; Coloration; Esthetics; Spectrophotometry